The "impacts cause injury" hypothesis: Running in circles or making new strides? - Gruber, A. H. (Journal of Biomechanics, 2023)
Some of the earliest biomechanics research focused on running and the ground reaction forces generated with each step. Research in running gait accelerated in the 1970's as the growing popularity in running increased attention to the musculoskeletal injuries sustained by runners. Despite decades of high-quality research, running remains the most common cause of exercise-related musculoskeletal injuries and rates of overuse running-related injuries (RRI) have not appreciably declined since the research began. One leading area of running gait research focuses on discrete variables derived from the vertical ground reaction force, such as the vertical loading rate. Across sub-disciplines of running gait research, vertical loading rate is often discussed as the primary and undisputed variable associated with RRI despite only low to moderate evidence that retrospectively or prospectively injured runners generate greater vertical loading rates than uninjured counterparts. The central thesis of this review is that relying on vertical loading rate is insufficient to establish causal mechanisms for RRI etiology. To present this argument, this review examines the history of the `impacts cause injury` hypothesis, including a historical look at ground reaction forces in human running and the research from which this hypothesis was generated. Additionally, a synthesis of studies that have tested the hypothesis is provided and recommendations for future research are discussed. Although it is premature to reject or support the `impacts cause injury` hypothesis, new knowledge of biomechanical risk factors for RRI will remain concealed until research departs from the current path or adopts new approaches to previous paradigms.